Penerapan Manajemen Risiko Kredit Dan Likuiditas Dalam Memberikan Pinjaman Dan Pembiayaan Kepada Anggota (Studi Pada BMT Nashrul Umam Balen) - Aris Zulianto; Nimas Dewi Lestari (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2022)
Based on the regulation of the Financial Services Authority (OJK) regarding the implementation of risk management in Islamic microfinance institutions, including the management of credit risk and liquidity risk. Credit risk (financing risk) is a risk that occurs due to the inability of the borrower and/or others to pay dependents to financial institutions. Whereas Liquidity risk is the risk that occurs as a result of NBFI liquidity management (Non-Bank Financial Services Institution) which failed. The purpose of this research is to know the application of risk management in providing financing to members. In this research, the author used a qualitative approach with a descriptive method and type of case study research on the object. With this methodology, the author describes the application of management credit and liquidity, methods of financing decisions, and integration of risk management in financing. The research results obtained are: (1) The application of risk management is to reduce financing so that NPL (Non-Performing Loan) financial institutions remain below standard; (2) In making financing decisions, the marketing department is required to: observe the main principle, namely 5C which relates to the overall state from prospective members, including character (character), capital (capital), capacity (ability), collateral (guarantee), and condition of the economy (state of the economy); (3) In the implementation of day-to-day operations of risk management integration credit and liquidity are indispensable in providing loans and financing to members. This is due to integration in implementation risk management for credit and liquidity risk can have implications for the liquidity position of BMT.